AAV9‐mediated AIRE gene delivery clears circulating antibodies and tissue T‐cell infiltration in a mouse model of autoimmune polyglandular syndrome type‐1 - Sarah Almaghrabi; Mimoun Azzouz; Rachid Tazi Ahnini (Clinical & Translational Immunology, 2020)
Abstract Objectives Autoimmune polyglandular syndrome type‐1 (APS‐1) is a monogenic recessive disorder characterised by multiple endocrine abnormalities, chronic mucocutaneous candidiasis and high titres of serum autoantibodies. To date, no curative treatment is available; current therapies manage the symptoms rather than treating the cause and have major side effects. APS‐1 is caused by mutations in the autoimmune regulator (AIRE) gene. AIRE mediates central tolerance by directing the ectopic expression of tissue‐specific antigens (TSAs) in medullary thymic epithelial cells, causing the deletion of self‐reactive thymocytes. Therefore, loss‐of‐function mutations in AIRE result in a multisystem autoimmune disease. Because of the monogenic aetiology of APS‐1 and availability of an APS‐1 mouse model, we have explored the option of restoring functional AIRE using adeno‐associated virus serotype 9 (AAV9). Methods The efficacy of AAV9‐AIRE (AAV9 carrying AIRE cDNA) gene therapy was assessed in an APS‐1 mouse model. We performed intrathymic injection of AAV9‐AIRE into APS‐1 mouse model using ultrasound imaging technique to accurately locating the thymus. We evaluated the efficiency of this approach alongside measures of autoimmunity and histology of target tissues. Results Intrathymic injection of AAV9‐AIRE demonstrated high transduction efficiency and restored AIRE expression in the thymus. AIRE gene delivery led to a significant increase in TSA expression, and importantly a significant reduction of serum autoantibodies in treated versus control mice, which fell to near‐undetectable levels by 4 weeks post‐treatment. Furthermore, histological analysis of treated animals showed near‐normal tissue morphology with no lymphocytic infiltrations, a hallmark of untreated Aire‐deficient mice. Conclusion This study has demonstrated the feasibility of AAV9‐AIRE as a vehicle for gene therapy for APS‐1.